FACTORS AFFECTING MEDICATION ADHERENCE LEVEL IN DIABETES MELLITUS PATIENS: A LITERATURE REVIEW - Sutini, Kristina; Rejeki, Dwi Sarwani Sri; Wijayanti, Siwi Pramatama Mars (Lux Mensana: Journal of Scientific Health, 2023)
Introduction. Diabetes Mellitus is a disease that affects many Indonesian people. This research aims to review articles regarding factors associated with the level of adherence to diabetes mellitus treatment. Method. The data was obtained from an electronic database of Google Scholar between 2015-2021, with the keywords "Diabetes Mellitus, medication adherence factor." From the 9950 articles found, 950 articles were relevant and 10 articles were selected for review. Results & Analysis. This literature study was obtained from 10 articles that met the inclusion and exclusion criteria. Based on the review of the article, it is known that there are factors related to the treatment of diabetes mellitus, including age, knowledge, motivation, social (family support and health workers), education, and psychological factors. Discussion. Family support, high level of knowledge, role of health workers, age, gender, and high motivation to conduct the treatment have an effect on treatment adherence of diabetes mellitus patients.